1991
DOI: 10.1136/emj.8.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Anterior dislocation of the restrained shoulder: a seat-belt injury.

Abstract: SUMMARYThe reduction in morbidity and mortality since the enforcement of seat-belt usage is well documented. Complications from the belt are also reported and the authors present anterior dislocation of the restrained shoulder, an injury not previously described.The mechanism of injury is explained and a change to the present standard of restraints is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Intra-peritoneal rupture of distended urinary bladder may occur when the horizontal strap of the seatbelt increases the intra-vesical pressure [ 52 ]. Blunt traumatic aortic rupture [ 53 ], sternal fractures [ 41 ], clavicle fractures [ 32 ] and shoulder dislocations [ 54 ] were also reported as a complication of seatbelts. Cervical spinal injuries were noticed to be higher in restrained children than non-restrained children [ 19 , 32 , 55 ].…”
Section: Seatbelt-related Injuriesmentioning
confidence: 99%
“…Intra-peritoneal rupture of distended urinary bladder may occur when the horizontal strap of the seatbelt increases the intra-vesical pressure [ 52 ]. Blunt traumatic aortic rupture [ 53 ], sternal fractures [ 41 ], clavicle fractures [ 32 ] and shoulder dislocations [ 54 ] were also reported as a complication of seatbelts. Cervical spinal injuries were noticed to be higher in restrained children than non-restrained children [ 19 , 32 , 55 ].…”
Section: Seatbelt-related Injuriesmentioning
confidence: 99%
“…Quantitative shotgun proteomics is now widely used as a potent technology for discovery-based analysis of complex biological systems. The approach of immunoaffinity enrichment followed by mass spectrometry allows identification of low abundance tyrosine phosphorylated proteins (22). A global study has identified several oncogenic kinases such as EGFR, c-MET, PDGFR␣, DDR1, and novel ALK and ROS fusions in non small cell lung cancer (NSCLC) cell lines (23) and tumor specimens (24).…”
mentioning
confidence: 99%
“… 2 We found one report in the literature addressing the relationship between anterior dislocation of the restrained shoulder and seatbelts. 3 We recently treated a restrained driver and a restrained front-seat passenger who had contra-lateral (mirror) anterior dislocation of the shoulders. Mirror injuries caused by 3-point seatbelts may involve both the driver and the front-seat passenger.…”
mentioning
confidence: 99%